2010
DOI: 10.1089/cyber.2009.0137
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Children and Adolescents Engaged in Cyberbullying to Matched Peers

Abstract: Although characteristics of traditional bullying participants have been identified and studied for years, research on cyberbullying is limited. The purpose of this study is to expand the literature on cyberbullying with a particular focus on the relationships among cyberbullying characteristics, typical social activities, and more traditional forms of bullying. The typical activities and experiences with traditional bullying and cyberbullying of 52 children ages 11 to 17 were compared to those of 52 matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 9 publications
0
41
0
8
Order By: Relevance
“…The limited number of studies that address the overlap between school and cyberbullying victimization has wide variation in findings, indicating that anywhere from about one third to more than three quarters of youths bullied online are also bullied at school. 11,13,14 The distinct features of cyberbullying have led to questions about the sociodemographic characteristics of cyberbullying victims compared with those of school bullying victims. Although numerous studies of school bullying have found that boys are more likely to be victims, 15,16 the extent of gender differences in cyberbullying is unclear.…”
mentioning
confidence: 99%
“…The limited number of studies that address the overlap between school and cyberbullying victimization has wide variation in findings, indicating that anywhere from about one third to more than three quarters of youths bullied online are also bullied at school. 11,13,14 The distinct features of cyberbullying have led to questions about the sociodemographic characteristics of cyberbullying victims compared with those of school bullying victims. Although numerous studies of school bullying have found that boys are more likely to be victims, 15,16 the extent of gender differences in cyberbullying is unclear.…”
mentioning
confidence: 99%
“…De igual forma, Twyman et al (2010) encuentran que tanto los agresores en línea como las víctimas, e incluso un tercer grupo de agresores-victimizados, pasan de media mayor tiempo utilizando el ordenador. También cabe destacar, por ejemplo, las conclusiones a las que llega el autor de otro estudio en el que la frecuencia del uso de Internet es el factor más robusto en la explicación de las conductas de acoso en línea (Erdur-Baker, 2010).…”
Section: Frecuencia En El Uso De Internetunclassified
“…Así, las víctimas de bullying también sue-len ser víctimas de cyberbullying (Hinduja y Patchin, 2008;Juvonen y Gross, 2008;MacDonald y Roberts-Pittma, 2010;Smith et al 2008;Sontag, Clemans, Graber y Lyndon, 2011;Twyman, Saylor, Taylor y Comeaux, 2010;Ybarra y Mitchell, 2004). Debemos pensar que existe una coherencia en el comportamiento de los adolescentes en la vida "on y off line" (Subrahmanyam, Smahel y Greenfield, 2006).…”
Section: Antecedentesunclassified
“…Estos resultados confirman la relación entre bullying y el cyberbullying. Muchas víctimas de bullying también son víctimas de cyberbullying (Hinduja y Patchin, 2008;Juvonen y Gross, 2008;MacDonald y Roberts-Pittma, 2010;Smith et al 2008;Sontag, Clemans, Graber y Lyndon, 2011;Twyman, Saylor, Taylor y Comeaux, 2010;Ybarra y Mitchell, 2004). La relación es superior en las chicas que en los chicos, confirmando los datos del estudio de Sourander et al (2010).…”
Section: Conclusionesunclassified